Potensi Antioksidan Ekstrak Daun Tempuyung (Shoncus Arvensis L.) Pada Dua Metode Pengeringan - Harun, Nurhidayati; Khairunnisa, Mutia (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
Drying is an important step in maintaining the stability of compounds, so that proper treatment of extracts is needed to get metabolite compounds to have efficacy. This study aims to determine the effect of extract drying method on the antioxidant activity of tempuyung leaves (Sonchus arvensis L.). Extract drying method used in conducting this research there are two methods, using waterbath and the combination of waterbath and oven is set at a temperature of 40 ° C. Antioxidant activity was carried out using the 1.1 diphenyl-2-picrilhydrazil (DPPH) method. Phytochemical screening result showed that the two samples using the waterbath extract drying method and the combination of waterbath and oven contained flavonoids. The average IC50 value of the tempuyung extract drying method was obtained (72,37±37,78) extract by dryng method using a combination of waterbath and oven (79,6±8,39) vitamin C as a positive control (5,46±7,874). The result of the analysis using one way ANOVA obtained a significance p<0,05,so there is a not difference in the IC50 value between the group of the extract drying method. In conclusiom, there was a not significant difference in the value of antoksidan activity for each sample dryied by different method.